2021
DOI: 10.1039/d1gc01069g
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free regioselective bromination of imidazo-heteroarenes: the dual role of an organic bromide salt in electrocatalysis

Abstract: This electrochemical protocol demonstrates an organic bromide salt i.e., tetra-n-butylammonium bromide (TBAB) as a brominating agent as well as an electrolyte for the regioselective bromination of several imidazo heteroaromatic motifs....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Roy's group 19 reported an electrochemical bromination by demonstrating the dual role of an organic bromide salt (tetra- n -butylammonium bromide, TBAB) as a brominating agent and as an electrolyte for the regioselective bromination of several imidazo-heteroaromatic molecules (Scheme 10). Mechanistic investigation revealed that this electrochemical bromination proceeded through the formation of molecular bromine by the anodic oxidation of bromide ions.…”
Section: Electrochemical Oxidative Brominationmentioning
confidence: 99%
“…Roy's group 19 reported an electrochemical bromination by demonstrating the dual role of an organic bromide salt (tetra- n -butylammonium bromide, TBAB) as a brominating agent and as an electrolyte for the regioselective bromination of several imidazo-heteroaromatic molecules (Scheme 10). Mechanistic investigation revealed that this electrochemical bromination proceeded through the formation of molecular bromine by the anodic oxidation of bromide ions.…”
Section: Electrochemical Oxidative Brominationmentioning
confidence: 99%
“…Then, isomerization of intermediate 85 produces intermediate 86 , which reacts with BrCCl 3 to afford intermediate 87 in the presence of TBAB through this photoredox catalysis. 44 Next, deprotonation of 87 gives compound 82 . Subsequently, compound 82 is oxidized by Ir( iv ) to afford the cation radical intermediate 88 by a SET process, which is further transformed into radical 89 .…”
Section: Introductionmentioning
confidence: 99%
“…(Scheme 1c). [12] Inspired by these studies, we herein design a one-pot reaction using 2-bromo-1phenylethan-1-one, 2-aminopyridine and N,N-dimethylaniline.…”
mentioning
confidence: 99%
“…Inspired by this work, several solvents such as MeCN, THF, dioxane, toluene, MeOH, DMF, DMSO, and H 2 O were evaluated; DMSO was found to be the best solvent (Table 1, entries 2-9). Based on these results, the effect of the reaction time was evaluated, and the desired product 4 a was obtained in 75% yield by prolonging the reaction time to 24 h. However, when the reaction time was increased to 48 h, the yield decreased slightly (Table 1, entries [10][11][12][13][14]. Temperature is also an important factor for the synthesis of the desired compounds.…”
mentioning
confidence: 99%